Strengthening cooperation and security in South Asia post 9/11 - Sobhan, Farooq (University Press Ltd., 2004)
Contributed papers presented at two regional conferences organized by Bangladesh Enterprise Institute in July 1-2, and September 23-24, 2003 at Dhaka, Bangladesh.